Quantification of tidally-influenced seasonal groundwater discharge to the Bay of Bengal by seepage meter study - Debnath, P.; Mukherjee, Abhijit (Elsevier BV, 2016)
Submarine groundwater discharges (SGD) play a major role in solute transport and nutrient flux to the ocean. We have conducted a spatio-temporal high-resolution lunar-tidal cycle-scale seepage meter experiment during pre-monsoon and post-monsoon seasons, to quantify the spatio-temporal patterns and variability of SGD, its terrestrial (T-SGD) and marine components (M-SGD). The measured daily average SGD rates range from no discharge to 3.6 m 3 m -2 d -1 during pre-monsoon season and 0.08-5.9 m 3 m -2 d -1 during post-monsoon seasons, depending on the tidal pattern. The uncertainty for SGD measurement is calculated as ±0.8% to ±11% for pre-monsoon and ±1.8% to ±17% for post-monsoon respectively. A linear, inverse relationship was observed between the calculated T-SGD and M-SGD components, which varied along the distance from the coast and position in the tidal-cycle, spatial and temporal (daily) variations of seepage rates within the lunar tidal cycle period distinctly demonstrate the influence of tides on groundwater seepage rate. As an instance, for the identification of the bulk discharge location, the centroid of the integrated SGD rate has been calculated and found to be near 20 m offshore area. The average discharge rate per unit area further extrapolated to total SGD fluxes to the Bay of Bengal from eastern Indian coas t by extrapolation of the annual and seasonal fluxes observed in the study area, which are first direct/experimental estimate of SGD to the Bay of Bengal. Approximations suggest that in present-day condition, total average annual SGD to the Bay of Bengal is about 8.98 ± 0.6 × 10 8 m 3 /y. This is suggested that the SGD input to the ocean through the Bay of Bengal is approximately 0.9% of the global input from the inter-tidal zone and that has an implication on the mass balance of discharging solutes/nutrients to the global oceans. High T-SGD input is observed for all season, which is largest toward landward direction from the delineated saltwater-freshwater interface. The high magnitude of T-SGD could play an important role in mass balance of fresh water discharge and solute transport to the global ocean, thereby influence coastal ecohydrological systems.